Fungal inhibitory effect of Citrus Limon peel essential oil on Candida albicans - Iwan Hernawan; Desiana Radithia; Priyo Hadi; Diah Savitri Ernawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Oral candidiasis is an opportunistic infections due to Candida albicans that often found in people with HIV/AIDS. Anti-fungi, polyne and azole, are used in the treatment of oral candidiasis, but often cause persistence and recurrence. Citrus Limon peel contains terpenoids capable of inhibiting the synthesis of ergosterol, a component of the fungal cell wall that helps to maintain cell membrane permeability. Essential oil derived from citrus limon peel, thus, is expected to inhibit the growth of Candida albicans. Purpose: This research was aimed to know how essential oil derived from citrus Limon peel can inhibit the growth of Candida albicans. Method: This research was a laboratory experimental research carried out in three phases. First, essential oil was made with cold pressing method, and then the concentration of 100% was diluted to 50%, 12.5%, 6.25%, 3.125%, 1.56% and 0.78%. A test was conducted on the culture of Candida albicans in Sabouraud broth, accompanied by control (+) and (-). Second, the dilution of essential oil was conducted to alter the concentration with inhibitory power, from the strongest one to the weakest one, and then it was tested on the culture of Candida albicans. Third, spreading was carried out from liquid culture to agar media in order to measure the number of colonies. Result: Candida albicans did not grow on media with 100% essential oil treatment, but it grew on media with 50% essential oil treatment. In the second phase, dilution of 100%, 90%, 80%, 70%, 60% and 50% was conducted. The growth of Candida albicans was found on the treatment media of 60% and 50%. On the agar media, the growth occurred in the cultured medium treated with 70%. Conclusion: The minimum inhibitory power of essential oil derived from citrus Limon peel against Candida albicans was in the concentration of 80%. Essential oil derived from citrus Limon peel has antifungal effect and potential as a therapeutic agent for oral candidiasis.